Number Theory and Combinatorics A Collection in Honor of the Mathematics of Ronald Graham. - Landman, Bruce M., 1951-; Luca, Florian; Nathanson, Melvyn B. (Melvyn Bernard), 1944-; Nesetřil, Jaroslav; Robertson, Aaron, 1971- (Proceedings in mathematics., 2022)
The series is aimed specifically at publishing peer reviewed reviews and contributions presented at workshops and conferences. Each volume is associated with a particular conference, symposium or workshop. These events cover various topics within pure and applied mathematics and provide up-to-date coverage of new developments, methods and applications.